FINITE-STATE METHODOLOGY IN NATURAL LANGUAGE PROCESSING - Korzycki, Michal (Computer Science, 2020)
Rcccnt mathcmatical and algorithmic rcsults in thc field of fmite-state tcchnology, as well as thc increasc in computing powcr, havc constructcd thc basc for a ncw approach in natural languagc Processing.Howcvcr the task of creating an appropriatc model that would dcscribe thc phcnomcna of thc natural languagc is still to be achicvcd. In this papcr l’m prcscnting somc notions rclated to thc finitc-statc modclling of syntax and morphology.